Pengaruh Kompensasi, Motivasi Dan DisplinTerhadap Kinerja Karyawan Thr Sriwedari Solo - Pratama, Hendy; , Drs.M.Farid Wajdi,M.M.,Ph.D (2016)
This research was done in THR Sriwedari Solo with the purpose of examining and analyzing the effect of compensation to employee performance THR Sriwedari; test and analyze the influence of motivation on employee performance THR Sriwedari and test and analyze the effect on employee performance discipline THR Sriwedari This study used a sample of 80 respondents, the method of data collection using the questionnaire. Analysis tools used are: testing instruments of data (validity and reliability testing), classical assumption (normality test, multicollinearity and test heteroskedastisitas) and test hypotheses (multiple linear regression analysis, test the coefficient of determination (R2), F test and test t). The results of data analysis can be obtained as follows: (1) there is significant influence compensation to performance. (2) there is a significant influence on the performance motivation. (3) there is a significant influence on the performance discipline. Thus the model is used appropriately (fit) and simultaneously variable compensation, motivation and discipline to performance. Based on the coefficient of determination (R2) of 0.877, this means that the independent variable in the model is able to explain the variations in the performance of employees in THR Sriwedari 87.7% and 12.3% is explained by factors or other variables outside the model